2009
DOI: 10.1007/s12517-009-0080-y
|View full text |Cite
|
Sign up to set email alerts
|

Serpentinites and their tectonic signature along the Northwest Zagros Thrust Zone, Kurdistan Region, Iraq

Abstract: Two types of serpentinized peridotites are distinguished within the Northwest Zagros Thrust Zone (NW-ZTZ) in Kurdistan region of Iraq. One is found as lower members of ophiolite sequences, such as the Mawat and Penjwin ophiolites of the upper Cretaceous age. The other is represented by intraformational isolated serpentinite bodies in Betwat, Qaladeza, and Qalander areas within the Walash-Naopurdan volcano-sedimentary unit of the Paleocene to Eocene paleo-arc tectonic setting. Serpentinites within the NW-ZTZ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The ultramafic rocks are classified into three groups: the first is dunite, which is composed mainly of fresh olivine, some of which show serpentine minerals around the rims and within fractures. Previous studies [32] have shown that the serpentine in these rocks is mostly chrysotile that formed at high temperature. Kink and deformation bands appear in dunite with disseminated chromite.…”
Section: Petrographymentioning
confidence: 85%
See 1 more Smart Citation
“…The ultramafic rocks are classified into three groups: the first is dunite, which is composed mainly of fresh olivine, some of which show serpentine minerals around the rims and within fractures. Previous studies [32] have shown that the serpentine in these rocks is mostly chrysotile that formed at high temperature. Kink and deformation bands appear in dunite with disseminated chromite.…”
Section: Petrographymentioning
confidence: 85%
“…Mawat ultramafics show false bedding because of parallel fractures (Fig. 4 a and b), and are variably serpentinized [32] and rich in chromite pods 32, 33. The harzburgite and dunite are cut by some fresh clinopyroxene dykes (Fig.…”
Section: Regional Geologymentioning
confidence: 99%
“…Mineralogical and chemical data from meta harzburgite of the Penjween ophiolite indicate that the parent olivine and spinel contain up to 0.4 wt. % and 1.2 MnO respectively (Mohammad, 2011). Meanwhile up on hydrothermal alteration the products of these two minerals represented by chromium magnetite and serpentine show decreasing MnO to 0.1 and 0.25 wt.…”
Section: Proposed Proposal For the Mn 2+ Sourcementioning
confidence: 93%
“…1c). The Penjween ophiolite consists of about 300 m thick mantle sequences mostly serpentinized harzburgite with some restricted dunite, pyroxenite veins and chromite pods to the southwest, occupying the summit of Mlakawa mountain, to the west followed by about 2 Km crustal sequences represent by various types of gabbro's (Ali and Rostum, 2021), dykes of diorite and volcanic rocks at the Mlakawa mountain slope and base respectively (Mohammad, 2011;Mohammad et al, 2021). Within the volcanic units occasionally bolder of metalliferous recrystallized quartz dominated rock occurs north of the Kani Manga village.…”
Section: Penjween Ophiolitementioning
confidence: 99%
See 1 more Smart Citation